Intra- and Inter-Specific Variation in Edible Jellyfish Biomarkers and Implications for Origin Traceability and Authentication - Wang, Yaxin; Gong, Yi; Zhang, Jian; Tang, Yi; Shi, Xiaofei; Shi, Jiangao (Frontiers in Marine Science, 2021)
With the continuous development of jellyfish fisheries and food products around the world, an effective traceability system has become increasingly prominent. This study provides insight into the origin traceability and authentication of two commercially important jellyfish species, flame jellyfish Rhopilema esculentum and Nomura’s jellyfish Nemopilema nomurai, while investigating the intra- and inter-specific variation in fatty acid (FA) profiles and carbon and nitrogen stable isotope ratios (δ13C and δ15N). Results showed significant differences in FA profiles and isotopic values in fresh bell tissues between wild and farmed R. esculentum and among geographic origins, possibly due to different food sources, nutritional status, and energy costs that each group experiences at a given location. The linear discriminant analysis indicated that δ13C, δ15N, C16:0, C17:0, C18:0, C16:1n7, and C20:5n3 were suitable discriminatory variables with a high rate of correct classification for distinguishing origins of R. esculentum. In addition, inter-specific FA profiles/biomarkers, combined with isotopic values, suggests the variety of dietary sources and trophic positions of sympatric similar-sized R. esculentum and N. nomurai and the potential use of biomarkers, especially stable isotope analysis, for distinguishing sympatric jellyfish species. These results highlighted the complementarity of FA and stable isotope analyses and provide an alternative approach for improving the origin traceability and authenticity evaluation of untreated edible jellyfish. Furthermore, this study adds new information regarding the biochemical compositions of jellyfish species.